Susceptibility of aedes aegypti and culex quinquefasciatus larvae to gedunin-related limonoids - Gurulingappa, Hallur; Tare, Vrushali; Pawar, Pushpa; Tungikar, Vijay; Jorapur, Yogesh R.; Madhavi, Sriram; Bhat, Sujata V. (Chemistry & Biodiversity, 2009)
The major non-azadirachtin limonoids such as gedunin (1), epoxyazadiradione (3), nimbocinol (4), and nimolicinol (5) from Azadirachta indica A. Juss ('neem') and their derivatives were evaluated for their toxic action against fourth instar larvae of Aedes aegypti L. and Culex quinquefasciatus SAY. Gedunin exhibited 100% toxic action against both the mosquito larvae at 50 and 10 ppm. Epoxyazadiradione and epoxynimolicinol also showed significant toxicities (>= 50%) against larvae of both mosquito species at 50 ppm. These neem limonoids can have benefits in mosquito-control programs.